Congestion pricing, air pollution, and individual-level behavioral responses - Elisabeth T. Isaksen; Bjørn G. Johansen (University of Oslo, Department of Economics, 2021)
This paper shows that differentiating driving costs by time of day and vehicle type help improve urban air quality, lower driving, and induce adoption of electric vehicles. By taking advantage of a congestion charge that imposed spatial and temporal variation in the cost of driving a conventional vehicle, we find that economic incentives lower traffic and concentrations of NO2. Exploiting a novel dataset on car ownership, we find that households exposed to congestion charging on their way to work were more likely to adopt an electric vehicle. Heterogeneity analyses show strong socioeconomic gradients in the transition towards low-emission cars.
Keywords: C33; H23; Q53; Q55; Q58; R41; R48; 330; air pollution; electric vehicles; transportation policies; congestion charging